Water front five star hotel, Alappuzha - Jacob, Mebin (SPA, Bhopal, 2013)
This thesis project aims to deal with the complete and comprehensive design methodology ranging from location of the site to complete visual renderings of the final project. This project has gone through each step by step following logical and comprehensive analysis of each parameter, constraint and ideas which were used in formulating and deciding the design thought process. Case studies were duly done of leading examples both within Indian and literature studies of hotels abroad. Overall, each step has been collated and corroborated under a panel of jury members comprised of experts on the subject. This thesis report aims to give the reader with a clear and comprehensive idea of how the whole project was dealt with
Keywords: Water front; Architecture